Factors limiting adherence to antiepileptic treatment: A French online patient survey. (22nd September 2017) - Laville, Flora; Montana, Marc; Roux, Nicolas; Rathelot, Pascal; Giorgi, Roch; Vanelle, Patrice
Summary: What is known and objective: There are various reasons why antiepileptic treatment can fail. One is drug‐resistant epilepsies, but non‐adherence, or poor adherence, to treatment may make some patients' treatment ineffective. The consequences of poor adherence include treatment failure or introduction of more complex treatments involving greater toxicity with uncertain prognosis. This study contributes to a critical research area focused on antiepileptic drug adherence and aims to assess the main factors limiting adherence, as well as psychosocial factors influencing on risk of non‐adherence. Methods: An opinion survey was conducted among patients and parents of children treated for epilepsy and members of a French online support group. Results and discussion: A total of 263 questionnaires were collected. Of the patients, 79% said they never forget their medication, whereas 21% admitted occasional or frequent omissions. The main treatment‐related factors that can limit adherence were adverse effects (limiting factors reported for 70% of patients) and number of tablets or number of intake per day (limiting factors reported for 32% of patients). Galenic (liquid) formulation (18%), drug taste (18%), tablet size (14%) and concern about the perception of others (17%) were cited in roughly equivalent terms as limiting adherence to treatment. Among the 55 patients who were genuinely non‐adherent to their treatment, the occupational difficulties induced by following the treatment were a main cause of non‐adherence. What is new and conclusion: Improving adherence in patients with epilepsy is a difficult and complex problem. Community pharmacists could play a major role in the determination of patients' adherence and should be aware of the risk of non‐adherence. Abstract : This study focused on antiepileptic drug adherence and aims to assess the main factors limiting adherence. Main factor reported by the patients limiting good adherence is side effects. Outings and holidays are risky situations affecting patients' adherence.